The Relation between Asthma Control and Quality of Life in Children - M. Banjari; Y. Kano; S. Almadani; A. Basakran; M. Al-Hindi; T. Alahmadi (International Journal of Pediatrics)
Background. Asthma is a common chronic illness worldwide. Asthmatic children are forced to alter their way of living to avoid its complications or exacerbations, which negatively affects their psychological and social well-being. High prevalence of behavioral and emotional difficulties was noticed among children with asthma. Methods. Cross-sectional study that was conducted over 8 months involving asthmatic children within the ages of 7-17 years presenting to two governmental hospitals in Jeddah, Saudi Arabia. Three questionnaires were used: asthma control test, the strengths and difficulties questionnaire, and the pediatrics asthma quality of life questionnaire. Using SPSS, Pearson’s chi-square and independent sample t-tests were used to find associations. Results. Among the 106 respondents, 84% of the sample had poor asthma control. Significantly poorer quality of life was observed in children with uncontrolled asthma (p = <0.001). Children with controlled and uncontrolled asthma were equally affected psychosocially with no relation between asthma control and their psychosocial well-being (p = 0.58). Conclusion. The majority of asthmatic children were uncontrolled with poor quality of life. This study recommends that the psychosocial well-being should be assessed during clinic visits for a better holistic approach and effective improvement of outcome. Further researches are needed to study the psychological effect of asthma.